2017
DOI: 10.1007/s40801-017-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Drug-Related Problems and Associated Factors at a Clinical Pharmacist Service-Naïve Hospital in Northern Sweden

Abstract: BackgroundPolypharmacy and increased sensitivity to side effects cause adverse drug events, drug–drug interactions and medication errors in the elderly.ObjectiveThe objective of this study was to investigate the prevalence and type of drug-related problems and associated factors among patients admitted to a clinical pharmacist service-naïve medical ward in an inland hospital in northern Sweden.MethodsDuring September–November 2015 and February–April 2016, clinical pharmacists working as part of a ward team on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
51
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 34 publications
15
51
4
1
Order By: Relevance
“…e difference could be attributed to differences in training levels of prescribers, availability of support systems, and composition of the health care team in these hospitals. Nonetheless, similar prevalence rates (66-75%) were also reported in different studies [20,[27][28][29][30]. e most frequently encountered DRPs were inappropriate dosing (high and low dose) followed by needs additional drug therapy and nonadherence to the prescribed medications.…”
Section: Discussionsupporting
confidence: 74%
“…e difference could be attributed to differences in training levels of prescribers, availability of support systems, and composition of the health care team in these hospitals. Nonetheless, similar prevalence rates (66-75%) were also reported in different studies [20,[27][28][29][30]. e most frequently encountered DRPs were inappropriate dosing (high and low dose) followed by needs additional drug therapy and nonadherence to the prescribed medications.…”
Section: Discussionsupporting
confidence: 74%
“…The analysis of the medication profile of the participants revealed that drugs belonging to the ATC groups "Alimentary tract and metabolism", "Cardiovascular system", and "Nervous system" were the most prescribed drugs. These groups of drugs are frequently associated to an increased prevalence of suffering from drug-related problems [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…15 However, the reported findings in our study are considered relatively higher in comparison with previous studies which reported 1.29, 1.53 and 1.93 DRPs per patient, respectively. 6,13,21 This shows that the frequency and type of identified DRPs may vary according to the setting. Accordingly, this variation may postulate some…”
Section: In Ward Managementmentioning
confidence: 93%
“…5 DRPs regarding the choice and use of drugs including interactions are relatively common among hospitalised patients which if not managed correctly may result in unwanted clinical and economic consequences. 6 Indeed, within various clinical specialities, the involvement of clinical pharmacists in patient care was found to positively enhance the efficiency of the overall process through providing medication reconciliation services to minimise the incidence and reoccurrence of DRPs and related consequences. 7 Moreover, the inclusion of clinical pharmacists in dispensing medical practices in Scotland, in the pharmaceutical care of patients has helped to optimise the impact of medication treatment programs in both the quantitative and qualitative service aspects.…”
Section: Introductionmentioning
confidence: 99%